Ultramorphological characteristics of Chrysomya megacephala (Diptera, Calliphoridae) eggs and its eclosion - de Oliveira David, Jose Augusto; Rocha, Thalita; Caetano, Flávio Henrique [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Chrysomya blowflies are originally from Africa and Australasia and were introduced in the American Continent, probably as a sheep parasite, in the 1970s. These flies are extremely important for medical-sanitary purposes and are useful to forensic entomology being used as an indicative of decomposition time in human corpses. The morphology of the larval and pupal stages of some species has been already studied by different authors demonstrating that it is possible to identify them in premature stages. In this study, Chrysomya megacephala egg ultramorphology was analyzed to describe its structure, generating data for further comparison between different species and genera. The blowflies were collected in Rio Claro city, SP, Brazil. Flies were attracted by fish carcasses and maintained in net cages; small portions of minced meat were placed in plastic pots for egg laying. Eggs were collected, fixed in alcoholic Bouin, prepared according to SEM routine and observed under Philips scanning electron microscope. C. megacephala eggs are oval with one flat face and another convex, measuring approximately 0.52 (+/- 0.03) mm of length and 0.12 (+/- 0.02) mm of width. The micropyle is circular in shape, with two perforations enclosed by countless small projections and is located in one of the extremities in the interface between the flat and convex faces. on the convex surface hexagonal imprints were observed, this surface is impermeable to water and gases. The flat surface has numerous round projections with different sizes, creating a permeable surface with a thinner chorion from which the larvae hatches. The larvae presents itself all wrinkled and with numerous cuticular projections with a thorn shape facing the posterior region. The cuticle projections with a thorn shape from C. megacephala larvae are probably a vestige of the thorns found in larvae of parasite Diptera. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Blowflie; Egg; Chorion; Plastron; Gas exchange; Larvae